Supporting environmentally sound decisions for waste management with LCT and LCA. - Manfredi, Simone (The International Journal of Life Cycle Assessment)
Introduction The amount of waste generated in Europe and, beyond, by our production and consumption patterns is significant. A proper waste management is essential in order to reduce detrimental environmental impacts. For the European Union, the general principles of good waste management are outlined in the Waste Framework Directive (2008/98/EC). This directive establishes a five step hierarchy of waste management starting with the preferred option of waste prevention followed by preparing waste for reuse, recycling and other recovery with disposal (such as landfill) as the last resort. Methods The European Commission encourages the use of life cycle thinking (LCT) to complement the waste hierarchy for a more environmentally sound and factual support to decision making in waste management. Results This has led to the development of a set of guidelines, tailored to the needs of different target audiences, which help apply LCT and quantitative tools such as life cycle assessment to waste management systems and strategies. The main aim of this paper is to present these guidelines, while also providing a structure overview on existing waste management criteria (e.g. the waste hierarchy), concepts and tools.